Heat transfer behaviors in a solar air heater channel with multiple V-baffle vortex generators - Tamna, Sombat; Skullong, Sompol; Thianpong, Chinaruk; Promvonge, Pongjet (My University, 2014)
The article presents a study on heat transfer augmentation in a solar air heater channel fitted with multiple V-baffle vortex generators (BVG). During the test air was passed through the test channel under a uniform wall heat-flux of the absorber plate. The fluid flow and heat transfer characteristics are presented for Reynolds numbers based on the channel hydraulic diameter ranging from 4000 to 21,000. The V-baffles are applied at a relative baffle height (in terms of blockage ratio, BR. =. b/. H=. 0.25) and attack angle of 45° with respect to the main flow direction. The use of BVG in the channel is to generate multiple longitudinal vortex flows through the test channel to increase turbulence intensity and stronger mixing of fluid between the core and the near-wall flow. Influences of three different baffle-pitch to channel-height ratios (PR. =. P/. H=. 0.5, 1 and 2) on heat transfer and pressure drop in terms of respective Nusselt number and friction factor (or energy loss for propelling air through the channel) are examined. Three BVG arrangements, namely, one BVG wall (or single BVG), in-line and staggered BVGs on two opposite walls are also investigated. The experimental result reveals that the smaller PR provides the highest heat transfer and friction factor for all BVGs. The in-line BVG yields higher heat transfer and friction loss than the staggered and the single BVG. However, the single BVG with PR. =. 0.5 yields the highest thermal performance. To shed light of heat transfer mechanism, a numerical work is also conducted to investigate heat transfer and flow friction characteristics in the channel fitted with 45° BVGs and in comparison, the numerical results are in good agreement with experimental data.
Keywords: Absorber plate; Heat transfer; Periodic flow; Vortex generators